2010
DOI: 10.1007/s00122-009-1257-1
|View full text |Cite
|
Sign up to set email alerts
|

Spatio-temporal dynamics of genetic diversity in Sorghum bicolor in Niger

Abstract: The dynamics of crop genetic diversity need to be assessed to draw up monitoring and conservation priorities. However, few surveys have been conducted in centres of diversity. Sub-Saharan Africa is the centre of origin of sorghum. Most Sahel countries have been faced with major human, environmental and social changes in recent decades, which are suspected to cause genetic erosion. Sorghum is the second staple cereal in Niger, a centre of diversity for this crop. Niger was submitted to recurrent drought period … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
31
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 53 publications
6
31
0
Order By: Relevance
“…Thus, we limit our inference of the detected patterns to say that there is no evidence for loss of genetic diversity within nyithin. Similar conclusions were drawn in studies of pearl millet and sorghum landrace diversity in Niger (11,58). A molecular comparison of sorghum landraces, sampled in the same villages separated by 26 y, marked by major social and environmental change, found no evidence of genetic erosion (11).…”
Section: Resultssupporting
confidence: 56%
See 1 more Smart Citation
“…Thus, we limit our inference of the detected patterns to say that there is no evidence for loss of genetic diversity within nyithin. Similar conclusions were drawn in studies of pearl millet and sorghum landrace diversity in Niger (11,58). A molecular comparison of sorghum landraces, sampled in the same villages separated by 26 y, marked by major social and environmental change, found no evidence of genetic erosion (11).…”
Section: Resultssupporting
confidence: 56%
“…All together, 358 plants from 220 accessions and seed lots were genotyped (Dataset S1). As in other large-scale assessments of sorghum genetic diversity (9,11,12), we included one individual per accession to infer population structure, and, as in ref. 8, we included more than one individual per seed lot for local-scale calculation of diversity indices, F ST among landraces, and NJ analysis.…”
Section: Methodsmentioning
confidence: 99%
“…In congruence with this study, Nybom (2004) compiled 79 microsatellite based studies and found that grand means for H o was lower than H e in 64 of these studies. Similarly, most of the genetic diversity studies in sorghum using SSRs (e.g., Ghebru et al 2002; Barro-Kondombo et al 2010; Deu et al 2010; Ngugi and Onyango 2012) supported this finding.…”
Section: Discussionmentioning
confidence: 67%
“…Soleri & Smith [56] and Louette et al [40], Tin et al [42] and Barry et al [44], Negri & Tiranti [26], Go ´mez et al [43], Parzies et al [41], Deu et al [45] took use of corn from USA and Mexico, rice from Vietnam and Guinea, kidney beans from Italy, common bean from Nicaragua, barley from Syria, sorghum from Niger as materials, studied the genetic and morphological diversity within populations of local varieties preserved in Gene-Bank and farms. They found that on-farm conservation can maintain or enrich genetic heterogeneity and diversity.…”
Section: Discussionmentioning
confidence: 99%
“…Related researchers analyzed the genetic diversity of different rice landraces in China using SSR molecular markers, successfully revealing changes in genetic diversity [37–39]. Most studies examining the influence of two conservation methods, i.e., on-farm and ex-situ conservation, on the genetic diversity of crop variety resources have focused on rice of different origins and varieties at the population level [4045], However, only Sun et al [39] and a few other researchers have performed comparative genetic analysis of the structures within single-origin pairs of crop landraces from on-farm and ex-situ conservation programs. Most of these studies have focused on Yunnan, while Guizhou and Guangxi have rarely been examined.…”
Section: Introductionmentioning
confidence: 99%